(untitled) (Environment & Health, 2018)
The current medical and demographic situation in Ukraine indicates an unsatisfactory state of health of the population, it is characterized by the high rates of morbidity, low birthrate and high death rate. Objective. We studied the modern regional features of the natural movement of the population and determined the typological groups of the districts by the results of childbearing activity. Materials and methods. Data from All-Ukrainian Census of the Population, State Statistics Service of Ukraine were used for the analysis of the demographic situation in Ukraine and Sumy region. We carried out the ranking of the districts of Sumy region by the indicators of natural increase (reduction) of the population in 2014-2016. Results. For the analysis of demographic changes in the region the three-year changes in the population of each district center was ranked. During the study the districts with comparatively favourable, intense and crisis demographic situationwere established. The three-years reduction of the number of the population in Sumy region was mainly due to the rural population (-3.13) in comparison with the population of urban settlements (-1.09). Atotal number of the population was established to be observed in all districts of the region but the factors of demographic processes were different. Isolated districts of the region have a similar picture of demographic changes that made it possible to distinguish four types of districts in the region according to the indicators of birthrate and mortality of the population. Demographic division into districts can serve as a basis for specific perspective medico-social measures for the mentioned regions. Sumy region belongs to the regions with a low indicator of average number of born children by the women at the age of 15 years old and older (2.0-2.1 children in comparison with the western regions of Ukraine where the average birthrate is more than 2.2 children). In the period of early reproductive age (20-24 years old) of the women of Ukraine and Sumy region, the average number of born children per 1 woman with the higher education makes up 1.09 and 1.06 respectively. The reproductive policy on the birth of two childrens is the most common one among the women of fertile age both in cities and in villages.